Architectural membranes on building refurbishment: contribution to functional performance and sustainability - Mendonça, Paulo (2016)
The use of building technologies that are environmentally more respectful is a growing concern in building design and construction. Considering its lightness, resilience and flexibility, membranes are becoming inevitable solutions in specific contexts of existing buildings’ refurbishment. A few millimeters membrane can be a self-supporting material and a selective sunlight filter capable of absorbing or reflecting the ultraviolet or infrared light whenever needed. These are some of the advantages of architectural membranes, but they can also be used to support thermal or acoustic insulation materials, as well as non-conventional thermal mass, such as phase change materials, in order to increase functional performance. Considering that in Portugal most of rehabilitation interventions are extensions (68.2%), this study presents a comparison between a membrane sunspace and the conventional sunspaces commonly used in the refurbishment of Porto’s bourgeois houses. Supported by previous studies from the first author the results’ analyses highlight an accurate overview on membrane material performance, in view to comfort requirements and sustainability of existing buildings.